Ethical Leadership and Counterproductive Work Behavior: The Mediating Role of Job Satisfaction - Dewanata, Muhammad Faaiz Pandu (Universitas Muhammadiyah Sorong, 2024)
Intense competition among public institutions underscores the need for effective human resource management. This study investigates Counterproductive Work Behavior (CWB), a concern for academics, professionals, and policymakers. CWB, a response to workplace dissatisfaction, is examined among 121 permanent nurses at Pandan Arang Hospital. Findings show that ethical leadership is negatively associated with CWB and positively linked to job satisfaction, which fully mediates the relationship between ethical leadership and CWB. The study contributes theoretically by advancing understanding of how ethical leadership influences CWB via job satisfaction, offering practical implications for organizations aiming to reduce CWB and promote ethical leadership practices.